The organization of housing : public and private enterprise in London - Harloe, Michael; Isaacharoff, Ruth.; Minns, Richard (London : Heinemann Educational [for the Centre for Environmental Studies], 1974)
The authors in this book explain what exactly is implied by the idea of a comprehensive policy, what the limitations are in the idea, what obstacles exist to the implementation of the concept, and finally, what a comprehensive housing policy means in terms of the whole question of the stratification of housing opportunities and its relevance to the spatial pattern of power and access in the city.
Includes bibliographical references and index.
rpm 24/01/2019
Loans
Keywords: Housing; Housing authorities